(untitled) (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
Sports organizations play an important role in developing athlete achievement and strengthening community participation, particularly in grassroots football clubs. Effective management strategies are needed to ensure sustainable athlete development, organizational stability, and community involvement in local sports activities. This study aimed to analyze the management strategy of the Diamond Tomoli Football Club in improving team achievement and increasing local community participation. This research employed a descriptive qualitative approach conducted in Tomoli Village, Toribulu District, Parigi Moutong Regency. The research informants consisted of one club manager, one coach, twenty players, and five community members. Data were collected through observation, interviews, questionnaires, and documentation. Data analysis used the Miles and Huberman interactive model, including data reduction, data presentation, and conclusion drawing. The findings revealed that the club’s management strategy had been implemented relatively well through structured training program planning, clear division of duties between managers and coaches, and routine training implementation. Performance improvement efforts were carried out through personal coaching approaches, motivational support, training targets, and periodic player evaluations. Community participation was categorized as relatively good, demonstrated through parental support, community involvement in tournaments, and increasing interest among young people to join the club. However, weaknesses were still identified in systematic training evaluation, improvement of players’ physical condition, and athlete regeneration programs. Therefore, strengthening organizational evaluation systems and expanding collaborative community involvement are necessary to support sustainable football club development.